EVALUATION OF THE USABILITY OF THE SIMPAUD WEBSITE IN SURABAYA CITY USING THE WEBSITE USABILITY EVALUATION METHOD (WEBUSE): WEBSITE USABILITY EVALUATION METHOD (WEBUSE) - Farah Nabilah Ardana; Aries Dwi Indriyanti (Universitas Negeri Surabaya, 2026)
One of the needs of educational institutions today is to provide access to data or information in the form of a management information system. In order to support quality learning for students from PAUD to TK, an effective and efficient information system is needed. The PAUD Information Management System (SIMPAUD) is here as a solution to help early childhood educators upload student information. SIMPAUD is a website managed and developed by the education office which is useful for teachers, especially educators from PAUD to TK. This study uses the Website Usability Evaluation (WEBUSE) method. The type of research used in this thesis is a quantitative method. This study obtained 110 respondents who were distributed to TK, KB, and PPT in Surabaya. Based on the evaluation of the SIIMPAUD website in terms of usability using the WEBUSE method, the total number of points was 0.59. This value indicates that the SIMPAUD website is included in the moderate category, which means that the SIMPAUD website still has several problems so that further research is needed so that these problems get better usability results. The usability dimensions that play an important role based on the results of the questionnaire data processing are Navigation and Links, because these categories are important in finding information in using it. The proposed solution recommendations based on the 4 variable usability problems are 10 solution recommendations.